2000
DOI: 10.1136/heart.84.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 expression in coronary circulation after coronary angioplasty as a risk factor for restenosis

Abstract: Objective-To investigate changes in cytokine expression in the coronary circulation induced by percutaneous transluminal coronary angioplasty (PTCA). Methods-The study involved 32 patients with ischaemic heart disease who underwent elective PTCA for isolated stenotic lesions of the left coronary artery. Ten patients had plain old balloon angioplasty, 10 had percutaneous transluminal rotational atherectomy, and 12 had stent implantation. Blood samples were drawn from the coronary sinus before and immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 24 publications
1
58
2
3
Order By: Relevance
“…Recently, we reported that IL-6 levels in the coronary sinus blood became significantly elevated after PTCA and that a positive significant correlation was observed between increased IL-6 levels and late restenosis. 50 From these findings, we are tempted to speculate that, in addition to its direct effects on vascular smooth muscle contraction and growth, 5-HT secreted from activated platelets may promote the initiation or progression of coronary atherosclerosis by activating IL-6 -mediated inflammatory processes in the vascular tissue. However, to prove our premise, further studies are necessary to determine whether 5-HT plays an inflammatory as well as thrombotic role in experimental models or patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that IL-6 levels in the coronary sinus blood became significantly elevated after PTCA and that a positive significant correlation was observed between increased IL-6 levels and late restenosis. 50 From these findings, we are tempted to speculate that, in addition to its direct effects on vascular smooth muscle contraction and growth, 5-HT secreted from activated platelets may promote the initiation or progression of coronary atherosclerosis by activating IL-6 -mediated inflammatory processes in the vascular tissue. However, to prove our premise, further studies are necessary to determine whether 5-HT plays an inflammatory as well as thrombotic role in experimental models or patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is an interesting report that the concentration of IL-6, a major inducer of CRP and SAA synthesis, in the CS increased immediately after PTCA and was higher in patients with late restenosis than in those without restenosis. 20) An elevated sino-arterial difference in the levels of IL-6 was reported in patients with acute coronary syndrome. 21) Thus, pro-inflammatory cytokines can be released by atherosclerotic coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…This includes P-selectin and integrins such as beta 2 -integrin Mac-1 (CD11b/CD18) (17). Local production of cytokines (eg, interleukin [IL]-1, IL-6 and tumour necrosis factor-alpha [TNF-α]) by activated macrophages, VSMCs and endothelial cells also play a major role in inducing an inflammatory reaction at the site of injury (18)(19)(20). Increased neointimal macrophage infiltration correlates with the extent of neointima formation in humans (21).…”
Section: Inflammationmentioning
confidence: 99%